Members, Junior Members, Associates and Junior Associates - Alphabetical List (6b70ca6f-d60e-4a5f-9988-430f4b102f0b) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1923)
Abadilla, Quirico A. Catanawan, Tayabas, P I '20 Abbey, Robert Graham, District Mgr., The W. W. Sly Mfg. Co, 50 Church St, New York, N. Y. '21 Abbott,-A. N., Mines Supt, Mazapil Copper Co., Ltd .. Concepcion del Oro, Zac., Mexico. '23 Abbott, Clarence E., Mgr, Mines & Quarries, Tenn. Coal, Iron & R R Co. 1242 Brown Marx Bldg, Birmingham, Ala. '04 Abbott, Louis Benjamin, Chief Engr, Consolidation Coal Co, Elkhorn Div . Jenkins, Ky. '15 Abeel, George H., Jr., Cons Min Engr... . Box 427, Santa Monica, Cal. '18 Abel, Albert E., Asst. to Pres., Valley Mould & Iron Corp Hubbard, Ohio. '19 Abel, Raymond L., Asst. Prof., Dept. of Pet. Refin , Univ. of Pittsburgh Pittsburgh, Pa. '28 Abernathy, George Elmer, Prof. of Geol. & Min., Kansas State Teachers College. Pittsburg, Kans '20 ||Abernethy, D. Carl, Jr. Min. Engr., Hudson Coal Co . Scranton, Pa '27 Abey, Hiroshi, Min. & Met. Engr., Min. & Met. Dept, The Higher Technical School, Osaka, Japan. '17 Aborn, Robert H., Instructor in Met, Harvard University Cambridge, Mass. '19 Abozeid, Mahmood, Pet. Production Engr., Marland Oil Co Ponca City, Okla. '20 Abraham, Arthur W., Geol, Richfield Oil Co. Box 788, Bakeisfield, Cal. '20 Abraham, W. E. V., Member, Geol Staff of Burmah Oil Co, Ltd Nyaunghla. Upper Burma, India. '23